Glycolipid-peptide conjugate vaccines enhance CD8+ T cell responses against human viral proteins. Issue 1 (December 2017) - Speir, M.; Authier-Hall, A.; Brooks, C.; Farrand, K.; Compton, B.; Anderson, R.; Heiser, A.; Osmond, T.; Tang, C.; Berzofsky, J.; Terabe, M.; Painter, G.; et al.
Abstract An important goal of vaccination against viruses and virus-driven cancers is to elicit cytotoxic CD8+ T cells specific for virus-derived peptides. CD8+ T cell responses can be enhanced by engaging help from natural killer T (NKT) cells. We have produced synthetic vaccines that induce strong peptide-specific CD8+ T cell responsesin vivo by incorporating an NKT cell-activating glycolipid. Here we examine the effect of a glycolipid-peptide conjugate vaccine incorporating an NKT cell-activating glycolipid linked to an MHC class I-restricted peptide from a viral antigen in human peripheral blood mononuclear cells. The vaccine induces CD1d-dependent activation of human NKT cells following enzymatic cleavage, activates human dendritic cells in an NKT-cell dependent manner, and generates a pool of activated antigen-specific CD8+ T cells with cytotoxic potential. Compared to unconjugated peptide, the vaccine upregulates expression of genes encoding interferon-γ, CD137 and granzyme B. A similar vaccine incorporating a peptide from the clinically-relevant human papilloma virus (HPV) 16 E7 oncoprotein induces cytotoxicity against peptide-expressing targetsin vivo, and elicits a better antitumor response in a model of E7-expressing lung cancer than its unconjugated components. Glycolipid-peptide conjugate vaccines may prove useful for the prevention or treatment of viral infections and tumors that express viral antigens.